Gerhard Richter, Panorama [a retrospective ; on the occasion of the exhibition "Gerhard Richter, Panorama", Tate Modern, London, 6 October 2011 - 8 January 2012 ; Neue Nationalgalerie, Berlin, 12 February - 13 May 2012 ; Centre Pompidou, Musée National d'Art Moderne, Paris, 6 June - 24 September 2012] - Richter, Gerhard 1932-; Godfrey, Mark 19XX-; Brill, Dorothée 1973- (Tate Publ., 2011)
Gerhard Richter is widely seen as one of the most important painters at work in the world today. Born in Dresden, Germany, in 1932, he left for the West in 1961, settling in Dusseldorf, where he held his first exhibition in 1963. He has exhibited internationally for the last five decades, including retrospectives in New York, Paris and Dusseldorf. He lives and works in Cologne. As the artist draws near to his eightieth birthday in 2012, Tate Modern in collaboration with the Neue Nationalgalerie, Berlin, and the Centre Pompidou, Paris, is staging a major retrospective exhibition. Exhibition: Tate Modern, London 6 October 2011 - 8 January 2012 / Neue Nationalgalerie, Berlin February - April 2012 / Centre Pompidou, Paris 6 June - 24 September 2012